DAMPAK DESENTRALISASI PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN PADA PENERIMAAN DAERAH KABUPATEN BATANG HARI - Sri Rosmawati (Universitas Batanghari Jambi, 2017)
This study aims to determine the effect of Construction Cost Index, Relative Poverty Index and Human Development Index for Fiscal Needs and to determine the relationship between the fiscal capacity of revenue sharing fund (DBH) and local revenue (PAD), The method used is the multiple regression analysis 2001-2011 and Pearson correlation test was conducted to determine the relationship between Needs Fiscal and Fiscal Capacity in personnel expenditures. In this study, it is found that the Construction Cost Index and relative poverty index negatively effect on Fiscal Needs, Human Development Index positive effect on Fiscal Needs, Pearson correlation of test results are known DBH positively and significantly associated with a P value or Sig 0,000 and Locally Generated Revenue positive and significant with a P value Fiscal Capacity sig 0.033 or less than 0.05. Fiscal Needs and Fiscal Capacity positively associated with personnel expenditures and significant with a P value or Sig 0.000 or less than 0.05.Key words: fiscal capacity, fiscal needs, fiscal, personnel expenditure, Revenue Sharing Fund (DBH), and Local Revenue (PAD).